Biodiversity, conservation, and hotspot atlas of Costa Rica: a dung beetle perspective (Coleoptera: Scarabaeidae: Scarabaeinae) - Kohlmann, Bert; Solís, Ángel; Elle, Ortwin; Soto, Xinia; Russo, Ricardo (Zootaxa, 2007)
This paper is an analysis of the distribution of areas of high species richness and endemicity based on dung beetles living in the different Holdridge life-zones of Costa Rica by using a geographic information system (GIS). Endemism was examined in relation to whether the species were shared with Nicaragua and/or Panama, or if they were strictly Costa Rican. The species composition of dung beetle distributions in the sampling areas and life-zones was evaluated. Species distribution was also analyzed in relation to altitudinal levels. The species richness and endemicity maps served as a base for doing a gap analysis and defining four different levels of high priority conservation areas. We also investigated what percentage of these priority areas is under some type of protection or conservation scheme and which of these areas should be enlarged. Also considered is the feasibility that these areas under protection have for enlargement, considering possible problems and interactions with present land-use. We include a list of all the recorded dung beetle species for Costa Rica, as well as their presence in the different Holdridge life-zones and their endemicity status. This study clearly demonstrates the need to include insects in biodiversity-endemicity studies because different and more detailed results are obtained in relation to vertebrate and plant-based studies.